UPF Campus VR: uma experiência virtual, imersiva e interativa na Universidade de Passo Fundo - Fernandes, Diógenes Pereira (2024)
The use of Virtual Reality as a marketing and tourism tool tends to create public empathy. Students interested in getting to know a university campus could have the opportunity to visit infrastructure spaces virtually, obtaining information about the courses offered in a different way, in addition to captivating the curiosity of the general public. With this in mind, this work presents the UPF Campus VR, a prototype that uses Virtual Reality devices and interaction techniques for 3D interfaces that provide the experience of an immersive visit to the University of Passo Fundo campus. It was developed using resources from the Unity game engine, the XR Interaction Toolkit package, and the Blender modeling tool. The work also carried out a pilot study to evaluate the UPF Campus VR, using technology acceptance instruments (5-point scale) and user experience (7-point scale). Eight volunteer participants took part in the experiment. The evaluations were very positive, highlighting the solution's ease of use (x = 4.50), its usefulness as a tool to support dissemination (x = 4.75), and original application aspects (x = 6.50) and interesting (x = 6.88) in user experience. The differentiators of the proposed approach are its availability as a virtual and immersive advertising tool, and significant advantages in terms of interactivity and engagement.